Long Non-Coding RNA RFPL3S Functions as a Biomarker of Prognostic and Immunotherapeutic Prediction in Testicular Germ Cell Tumor - Guo, Jie; Wang, Shuang; Jiang, Zhenzhen; Tang, Le; Liu, Zhizhong; Cao, Jian; Hu, Zhaolan; Chen, Xiao; Luo, Yanwei; Bo, Hao (Frontiers in Immunology, 2022)
The incidence of testicular germ cell tumor (TGCT) is currently on the rise worldwide, of which 15%-30% of patients have occur recurrence and metastasis. However, clinical methods for diagnosing TGCT and judging its prognosis remained inadequate. this study, we used the TGCT gene expression data in GEO and TCGA databases aimed to explore the possibility of testis-specific long-chain non-coding RNA (lncRNA) Ret finger protein-like 3S (RFPL3S) as a biomarker for TGCT diagnosis, prognosis, and treatment response. by reviewing the TGCT gene expression data in Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) databases. The cohort data and DNA methylation data of TGCT in TCGA were downloaded from TGCA, UCSC XENA, and GEO. The bioinformatic tools were used, including GEPIA2, Kaplan-Meier Plotter, LinkedOmics, UCSC XENA, Sangerbox Tools, GSCA, and Tumor Immune Dysfunction and Exclusion. Compared with normal testicular tissues, the RFPL3S expression was significantly reduced in TGCT, and was significantly negatively correlated with the patient’s Tumor, Node, Metastasis stage. Hypermethylation and low copy number of RFPL3S were present in TGCT, and low RFPL3S was associated with short disease-free and progression-free intervals. Silencing RFPL3S significantly enhanced the invasion ability and proliferation ability of TGCT cells as evaluated by Transwell and CCK-8 experiments. Additionally, RFPL3S expression was positively correlated with the infiltration of immune-activating cells such as B cells, CD8+ T cells, cytotoxic T cells, and natural killer cells, and negatively correlated with the infiltration of immunosuppressive cells such as Th17 and Th2. Higher RFPL3S expression was present in patients with immunotherapy benefits. In conclusion, we determined that the testis-specific lncRNA RFPL3S functioned as a tumor suppressor in TGCT and could be used as a prognostic predictor of TGCT, as well as a marker to predict the effect of TGCT immunotherapy.